Analisis Kualitas Air sebagai Air Bersih pada Sumber Mata Air Hutan Bambu di Desa Sumbermujur Kecamatan Candipuro Kabupaten Lumajang - Vikahadi, Nanda; Wicaksono, Aditya Pandu; Nugroho, Nandra Eko; Gomareuzzaman, Muammar; Prasetya, Johan Danu (Indonesian Journal Publisher, 2023)
Clean water is one of the basic needs that is needed and is an important concern in a residence for human survival. The condition of the springs is estimated to have experienced a decrease in water quantity due to human activities and changes in quality due to the change of dry and rainy seasons as well as traditional activities. This research aims to determine the quality and quantity of spring water based on physical, chemical and biological parameters based on RI Minister of Health Regulation No. 32 of 2017. These parameters are turbidity, color, TDS, temperature, odor, pH, Nitrate, Nitrite, Cr 2+, Iron, Mn, Total Coliform, E-Coli. The method used is a survey method for sampling and measuring discharge. The results show that the Total Coliform, E-Coli and Temperature parameters exceed the quality standards. This is an indication that there is a result of the dissolution of chemicals from the agricultural activities of local residents as well as the existence of the ruwatan tradition which uses organic materials put into ponds. Water quality that does not meet quality standards will affect public health and the surrounding environment.